CZEXWED: The unified Czech extreme weather database - Marek Kašpar; Miloslav Müller; Vojtěch Bližňák; Anna Valeriánová (Weather and Climate Extremes, 2023)
A crucial step in developing a strategy against natural hazards is the analysis of weather extremes in the past. Due to the multiplication of their impacts when occurring in a larger area, we strongly recommend not evaluating the extremes only at individual sites but assessing regional extreme weather events. The presented Czech Extreme Weather Database (CZEXWED) comprises six types of extreme events, namely, heat waves, cold waves, air temperature drops, windstorms, heavy precipitation events, and heavy snowfalls. To date, it covers the period 1961–2020. To minimize methodological differences in the process of evaluating various types of extreme weather events including compound events, we employed the weather extremity index (WEI), a universal indicator based on the evaluation of return periods of relevant variables. Each event is characterized not only by the WEI value but also by its spatial extent and duration.Heat and cold waves in Czechia generally reach higher WEI values than other types of extreme weather because they usually affect larger areas. The number and extremity of heat waves are increasing significantly, while the opposite may be true for cold waves and windstorms. Air temperature drops defined by declines in daily maximum air temperature are frequent in the warm half-year, but three of four top events occurred in January. Windstorms and heavy precipitation events prevailed in the cold and warm half-years, respectively, but weaker events of these types also occurred during the opposite season. A comparison of CZEXWED with event lists from the wider Central European region shows that Czech and Central European extreme events correspond well with each other.